Representation of Culture in English Textbook: A Content Investigation - Pulungan, Anni Holila; Kusmanto, Joko; Mukmin, Mohammad Jamil bin (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
Investigation of the usage of English language textbooks in educational institutions has been lacking, despite significant progress and changes on a global scale regarding the cultural dimension of learning English as a global language. This research thoroughly analyzes how culture is portrayed in English textbooks published by the Ministry of Education and Culture, specifically those under the title